Contest decisions are governed by own size and opponent size category in mangrove rivulus fish, Kryptolebias marmoratus. (December 2018) - Li, Cheng-Yu; Jones, Ryan; Earley, Ryan L.
Abstract : When confronted with social challenge, animals extract information from their environment to make adaptive behavioural decisions. The size of an individual relative to its opponent is a decisive factor that could influence contest decisions and the outcome of social competition. Animals may determine whether or not to engage in fights by assessing each other's fighting ability (mutual assessment), or solely based on their own fighting ability (self-assessment). Mangrove rivulus, Kryptolebias marmoratus, have been reported to utilize both assessment strategies depending on the stage and intensity of a contest. However, it is still unclear whether rivulus' contest decisions are determined by their own body size, perceptions of size differences between themselves and opponents, or by information conveyed by opponents' behaviour. In this study, we aimed to investigate whether rivulus of different sizes respond differently when encountering opponents of varied sizes. We provided rivulus with a 'stationary model opponent' to fight against, which can isolate the effect of size (and size differences) on aggressive performance without the potentially confounding effects of opponent behaviour. We hypothesized that animals would be more willing to initiate a contest and behave more aggressively when interacting with a size-matched opponent because differences in fighting ability are less easily perceived. As size asymmetries increase, however, differences in fighting ability should be more obvious to the animals and, thus, they should be less willing to initiate a contest and behave less aggressively. Our data support our hypothesis and reveal that, during early stages of a contest, opponent size alone does not affect an individual's contest decisions. Additional sources of information (e.g. about one's own body size) likely contribute to decisions about whether or not to initiate a fight. However, once individuals engage physically, their own body size, but not opponent size, becomes a predictor of their aggression towards opponents. Highlights: Information about own size and opponent size modulates rivulus' contest behaviour. Various information sources drive behavioural variation early on in a fight. Opponent size alone does not influence contest decisions. Interaction between own size and opponent size category affects contest initiation. Body size predicts aggressiveness during later stage of fights.